2010
DOI: 10.1375/prp.4.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Does Motivation to Migrate Matter? Voluntary and Forced African Migrants and Their Acculturation Preferences in New Zealand

Abstract: As there is no research on forced migration of African migrants to New Zealand, in particular on the interrelations among psychological motives to migrate and psychological acculturation preferences, the present study aims to address this gap. One hundred and five forced and voluntary African migrants to New Zealand completed a questionnaire, which included two measures (a) the Psychological Motives to Migrate (Tharmaseelan, 2005) and (b) the Psychological Acculturation Index (Mace, 2004). Demographic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the domain of social and community life, theoretical contributions can be found in Table 1 concerning how people’s implicit processes and biases mediate coping with changes through immigration into “their” communities (Pedersen & Fozdar, 2010); for making supportive attributions about appropriate forms of antipoverty interventions (Hastie, 2010); about new settlers’ adaptation patterns and styles (King, Welch, & Owens, 2010; Udahemuka & Pernice, 2010); and about the motivating qualities of social identity as a mediator for poverty reduction initiatives (Thomas, McGarty, & Mayor, 2010). These mediators are not part of the “culture of poverty,” but perhaps more constructively can be seen as part of the “culture[s] of daily life” (Kumar, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the domain of social and community life, theoretical contributions can be found in Table 1 concerning how people’s implicit processes and biases mediate coping with changes through immigration into “their” communities (Pedersen & Fozdar, 2010); for making supportive attributions about appropriate forms of antipoverty interventions (Hastie, 2010); about new settlers’ adaptation patterns and styles (King, Welch, & Owens, 2010; Udahemuka & Pernice, 2010); and about the motivating qualities of social identity as a mediator for poverty reduction initiatives (Thomas, McGarty, & Mayor, 2010). These mediators are not part of the “culture of poverty,” but perhaps more constructively can be seen as part of the “culture[s] of daily life” (Kumar, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, fear-of-failure economic motives (Winter-Ebmer, 1994) and the drive for mere financial betterment seem to be detrimental for the migrant (Doerschler, 2006). The beneficial effects of the motivation to explore, expand one`s horizons, gain intercultural knowledge and skills, enjoy freedom, and improve personally and professionally transpires from several studies (e.g., Doerschler, 2006;Udahemuka & Pernice, 2010). Indeed, self-determined and intrinsic motivation (Chirkov et al, 2007(Chirkov et al, , 2008Yang et al, 2018;Zhou, 2014), acculturation motivation (Chirkov et al, 2007(Chirkov et al, , 2008Dentakos et al, 2017;Kitsantas, 2004), and non-compelled motivation (Pinto et al, 2012) were shown to be generally beneficial for both the well-being and later adjustment success of various groups of migrants.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that premigration motivation is predictive of psychological or sociocultural adaptation but not necessarily of career success. Udahemuka and Pernice (2010) investigated whether the motives used by Tharmaseelan et al (2010) predicted the acculturation orientation of forced and voluntary African migrants in New Zealand. They found that migrants with exploration and family motives were more likely to embrace cultural adaptation orientation, whereas migrants with escape motives were more likely to prefer maintenance of their heritage culture.…”
Section: Goal Content In the Pre-migration Stagementioning
confidence: 99%
“…There is also a need for additional employment and educational support. Udahemuka and Pernice's (2010) study of African migrants in New Zealand found that forced and voluntary migrants differ according to their acculturation style which, as Murray reported, may influence whether forced migrants access mainstream services, form broad friendship support networks and enjoy positive psychological wellbeing.…”
Section: Further Insights Into Forced Migration and Disadvantagementioning
confidence: 93%